New Paradigm in Cell Therapy Using Sperm Head to Restore Brain Function and Structure in Animal Model of Alzheimer’s Disease: Support for Boosting Constructive Inflammation vs. Anti-Inflammatory Approach - Nafiseh Pakravan; Ardeshir Abbasi; Zuhair Mohammad Hassan (Journal of Immunology Research)
Alzheimer’s is characterized by accumulation of amyloid-β (Aβ) associated with insufficient clearance of toxicants from the brain establishing a chronic inflammation and other abnormalities in the brain. Inflammatory microglia and astrocytes along with abnormal lymphatics associated with insufficient clearance of Aβ and other toxicants from the brain establish a chronic inflammation. This causes abnormal choroid plexus, leukocyte trafficking, and hypoxic condition along with high levels of regulatory T cells (Tregs). There is no consensus among researchers regarding decreasing or increasing Tregs to achieve therapeutic effects. Different opposing studies tried to suppress or boost inflammation to treat AD. Based on reproductive immunology, sperm induces constructive inflammatory response and seminal-vesicle-fluid (SVF) suppresses inflammation leading to uterus remodeling. It prompted us to compare therapeutic efficiency of inflammatory or anti-inflammatory approaches in AD model based on reproductive immunology. To do so, SVF, sperm, or sperm head (from Wistar rat) was administered via intra-cerebro-ventricular route to Sprague Dawley rat AD model. Behavioral and histological examination were made and treatment groups were compared with control AD model and normal groups. Therapeutic efficacy was in the order of sperm head>sperm>SVF. Sperm head returned learning memory, Aβ, lymphatics, neural growth factors, choroid plexus function, Iba-1/GFAP, MHC II/CD86/CD40, CD38/IL-10, and hypoxia levels back to normal level. However, SVF just partially ameliorated the disease. Immunologic properties of sperm/sperm head to elicit constructive inflammation can be extended to organs other than reproductive. This nature-based approach overcomes genetic difference as an important obstacle and limitation in cell therapy, and is expected to be safe or with least side effects.